Plan estratégico de marketing para el taller Construmaq industrias, canton Quevedo, periodo 2014-2017 - Reyes Véliz, Mercedes Fernanda (2015)
This study focused on construction machinery industry balsera, industrialization requires machine according to the market; It is an opportunity for the workshop Construmaq Industries, in the city of Quevedo to build or manufactures the respective machinery to give more easily to companies that process and market the raft to foreign markets. In the implementation of customer surveys Construmaq Industries workshop, the results show a lack of building machines for processing the raft engaged in exporting; you need to have materials in stock in the shop for mechanical engineering must also make greater publicity to promote the product on the market. The research highlights the need to implement a marketing strategy that allows attract new customers and increase sales. In this paper the technical study, internal situational analysis and external financial study was conducted, and a tactical plan was created to implement marketing strategies, which positive results were obtained with the application of greater publicity and promoting applied on machines with greater market share We conclude that is necessary to implement a strategic marketing plan for the workshop Construmaq Industries to meet and achieve the desired improving administrative management which allows to present a sustainable project objetives.